Texture evolution during static recrystallization of cold-rolled magnesium alloys. (15th February 2016) - Zeng, Z.R.; Zhu, Y.M.; Xu, S.W.; Bian, M.Z.; Davies, C.H.J.; Birbilis, N.; Nie, J.F.
Abstract: Texture evolution in cold-rolled Mg-0.3Zn-0.1Ca, Mg-0.4Zn and Mg-0.1Ca (at.%) alloys during static recrystallization is monitored using a quasi - in - situ electron backscatter diffraction (EBSD) method. The quasi - in - situ EBSD results show that most of recrystallized grains formed in the early stage of recrystallization have randomised orientations in the ternary alloy and they grow uniformly during the recrystallization process. The formation and uniform growth of these recrystallized grains with randomised orientations give rise to a weak texture in fully recrystallized samples of the ternary alloy. A weak recrystallization texture also forms in the early stage of recrystallization in the two binary alloys, but it is gradually replaced by a strong basal texture via the preferential growth of recrystallized grains with specific orientations. The grain size in the ternary alloy is smaller than those in the two binary alloys at each stage of recrystallization, and the grain size distribution in the ternary alloy is significantly narrower than those in the two binary alloys after full recrystallization. Solute segregation to grain boundaries is observed in all three alloys in the fully recrystallized state. It is hypothesised that Zn and Ca atoms in the ternary alloy segregate strongly to high-energy boundaries of the recrystallized grains that would otherwise grow preferentially in the counterpart binary alloys, and that this co-segregation would significantly reduce the boundary mobility, by reducing grain boundary energy and enhancing solute dragging effect, and therefore lead to a more uniform growth of recrystallized grains with randomised orientations. Graphical abstract: